Estimating the impact of biosimilar entry on prices and expenditures in rheumatoid arthritis: a case study of targeted immune modulators. (31st December 2022) - Maksabedian Hernandez, Ervant J.; Graf, Marlon; Portelli, Alexandria; Shafrin, Jason
Abstract: Objective: To model changes in prices, utilization, and expenditures of targeted immune modulators (TIMs) for rheumatoid arthritis, accounting for biosimilar entry. Methods: Using IQVIA National Sales Perspective data between 2013 and 2019, we examined sales and expenditures of biologics and non-biological complex molecules, 20 quarters before and after patent exclusivity milestones. We estimated the impact of a molecule's exclusivity milestones and biosimilar entry on prices, using a regression discontinuity design (RDD). We then combined the RDD estimate with historical trends to assess the impact of adalimumab's exclusivity milestones on future TIM expenditures. Results: Changes in average molecule prices were associated largely with biosimilar uptake. For molecules with relatively high biosimilar uptake (>60%), prices fell considerably (−21.2% to −59.3%) one year after exclusivity milestones, whereas molecules with lower biosimilar uptake (<10%) experienced smaller price decreases (−2.4% to −8.4%). Average price reduction at the molecule level after biosimilar entry was not significant (−18.6%; p  = .657). When applying the RDD results after adalimumab's exclusivity milestones, its projected share of total TIM market expenditures decreased from 48.0% in 2019 to 26.0% in 2025, whereas expenditures on Janus kinase inhibitors increased from 4.0% to 34.0%. Conclusions: Biologics facing biosimilar competition may experience price decreases, potentially offering substantial savings to payers, patients, and society, although the magnitude of these estimates depends on biosimilar uptake. Formulary placement, along with manufacturer-payer dynamics, may also play a role in determining the impact on price and market uptake of biosimilars.